2018
DOI: 10.1186/s40834-018-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and factors associated with post-partum IUCD use among women who gave birth at bale zone health facilities, Southeast-Ethiopia

Abstract: BackgroundThe postpartum intrauterine contraceptive devices (PPIUCD) is the only family planning method for couples requesting highly effective, reliable, inexpensive, non-hormonal, immediately reversible, and long-acting contraceptive that can be initiated during the immediate postpartum period and it has no a negative effect on lactation. Despite these benefit, the acceptance and utilization of immediate PPIUCD were very low and the reasons for rejecting immediate PPIUCD usage have not been characterized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
66
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 13 publications
16
66
6
Order By: Relevance
“…Women who are educated are empowered to decide fertility control and can better understand the health information offered to them regarding the use of PPIUCD, Additional women who are educated were more likely to visit a health facility and receive counselling for different methods available in the health facility. This is in line also with a study done in Ethiopia where women with formal education were more likely to use PPIUCD compared with counterparts (12) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women who are educated are empowered to decide fertility control and can better understand the health information offered to them regarding the use of PPIUCD, Additional women who are educated were more likely to visit a health facility and receive counselling for different methods available in the health facility. This is in line also with a study done in Ethiopia where women with formal education were more likely to use PPIUCD compared with counterparts (12) .…”
Section: Discussionsupporting
confidence: 92%
“…The medical eligibility criteria WHO recommended it can be initiated during the immediate postpartum period and it cannot interfere with breastfeeding (10,11). The PPIUCD has shown that when it is initiated after delivery it can improve maternal and newborn health by preventing obstetrics complications such as maternal and newborn mortality and other health related complications associated with closed spaced pregnancy (12). Immediate post-partum period is an ideal time for PPIUCD when women are highly motivated to accept family planning methods (13) (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…agreed that insertion of IUD causes loss of privacy and 41.6% agreed that IUDs may impair future fertility (29). In another community based study cross-sectional study, nearly one-third (31%) of study participants disagreed with the statement "insertion of intrauterine contraceptive devices does not lead to loss of privacy".…”
Section: Factors Associated With Larc Methods Usementioning
confidence: 99%
“…Similar finding also obtained in Egypt, which is 23.7% of mother who gave birth in public health facilities used PPIUCD (7). Among mothers who gave birth at public health facilities in Ethiopia, only few proportion of them utilize PPIUCD (12.4%) (8).…”
mentioning
confidence: 99%